Development of Green Banking Concept in Banking Policy for Considering Environmental Protection - Hatikasari, Siti; Ganefi, Ganefi (Lembaga Contrarius Indonesia, 2023)
The principles of green banking can strengthen bank risk management strategies, especially related to the environment, and encourage banks to increase investment in environmentally friendly financing. Green banking has developed in its practice with the emergence of regulations, changes, or reconstruction of policies in the banking sector in Indonesia. Therefore, this study aims to examine and analyze the development of the application of green banking in banking policies. Then, it will also find out and analyze the importance of green banking in banking policies in fulfilling banking responsibilities in considering environmental protection in Indonesia. This chapter uses doctrinal legal research methods and is analyzed analytically and qualitatively. The role played by banking corporations is very significant in having a broad impact on the application and efforts to achieve the goals of the green banking concept. The weakness of policies in the banking sector and other implementing regulations in Indonesia has resulted in not a few violations occurring and resulting in damage to the existing environment. Clear regulations as legality in regulating the implementation of green banking and supervision and evaluation are needed to have a broad positive impact on the sustainability and preservation of nature.